"In the hospital, there will be nobody to pamper me": a qualitative assessment on barriers to facility-based delivery in post-Ebola Sierra Leone - Stefanie Theuring; Alimamy Philip Koroma; Gundel Harms (BMC, 2018)
Abstract Background Sierra Leone has one of the highest maternal mortality rates in the world. Encouraging the use of skilled birth attendance in health facilities is an important step in the endeavor to increase the number of safe deliveries. However, public trust in health facilities has been greatly damaged during the Ebola epidemic outbreak in Sierra Leone in 2014/2015, and little is known about external and intrinsic barriers to facility-based delivery (FBD) in the country since the end of the Ebola epidemic. Methods We conducted a qualitative study on FBD in Princess Christian Maternity Hospital, Freetown, which is the national referral maternity hospital in Sierra Leone. We performed six focus group discussions with providers, pregnant women and recent mothers surrounding experiences, attitudes and behaviors regarding FBD and potential barriers. Discussions were tape recorded, transcribed and evaluated through content analysis. Results Women in our study were overall technically aware of the higher safety linked with FBD, but this often diverged from their individual desire to deliver in a supportive and trusted social and traditional environment. Close relatives and community members seemed to be highly influencial regarding birth practices. Many women associated FBD with negative staff attitudes and an undefined fear. Logistic issues regarding transportation problems or late referral from smaller health centers were identified as frequent barriers to FBD. Conclusions More supportive staff attitudes and acceptance of an accompanying person throughout delivery could be promising approaches to increase women's confidence in FBDs. However, these approaches also imply revising health systems structures, like staff working conditions that are conducive for a friendly atmosphere, sufficient space in delivery wards allowing the women to bring a birth companion, or like the establishment of a reliable peripheral ambulance system to ensure transportation and fast referral.